Effects of Sulfaphenazole Derivatives on Cardiac Ischemia-Reperfusion Injury: Association of Cytochrome P450 Activity and Infarct Size - Yasuhiro Ishihara; Masaya Sekine; Ai Hamaguchi; Yusuke Kobayashi; Takashi Harayama; Mikio Nakazawa; Norio Shimamoto (Elsevier, 2010)
Cardiac ischemia-reperfusion injury is evoked by reactive oxygen species (ROS). We previously reported that sulfaphenazole (SPZ) attenuated cardiac ROS levels and ischemia-reperfusion injury in rats. SPZ has distinct two actions: a) elimination of ROS and b) inhibition of cytochrome P450 (CYP) that is responsible for ROS production. The aim of this study is to determine which action contributes to the attenuation of cardiac ischemia-reperfusion injury using SPZ and its derivatives [acetyl-SPZ (Ac-SPZ) and dichloro-SPZ (2Cl-SPZ)]. Administration of 2Cl-SPZ or SPZ prior to ischemia significantly reduced myocardial infarct size, myocardial lipid peroxides, and ROS levels. In addition, they inhibited rat cardiac CYP activity. However, Ac-SPZ neither reduced infarct size nor inhibited cardiac CYP activity. The three compounds had similar effects on ROS scavenging activity in that they scarcely scavenged hydrogen peroxide and superoxide anions but reduced hydroxyl radicals with the same efficacy. The serum concentration of each compound was almost the same until 24 h after reperfusion. Collectively, our findings indicate that the suppressive effects of SPZ and 2Cl-SPZ on ischemia-reperfusion injury are associated with the reduction of ROS levels, which is primarily due to a decrease in ROS production via inhibition of cardiac CYP, not via ROS scavenging activity. Keywords:: heart ischemia-reperfusion, reactive oxygen species, sulfaphenazole, cytochrome P450